Patterned surfaces of poly (lactic acid) and starch – poly (lactic acid) blend prepared by reverse breath figures, the effect of : solvent, substrate and vapour - Sousa, Nuno André Carvalho (2011)
Dissertação de mestrado integrado em Engenharia Biomédica (área de especialização em Biomateriais, Reabilitação e Biomecânica)